Development and validation of high-performance liquid chromatography method for determination of flunixin-meglumine and its impurities in preparations for veterinary use - Ivković, Branka; Zabelaj, Davor; Brborić, Jasmina; Čudina, Olivera (Archives of Pharmacy, 2022)
Flunixin is a non-steroidal anti-inflammatory drug, as well as an analgesic that has an antipyretic effect. In veterinary medicine, it is used as salt flunixin meglumine. Flunixin shows strong inhibition of the cyclooxygenase system involved in the development of inflammation. The decrease in the production of certain inflammatory mediators explains its analgesic, antipyretic and anti-inflammatory properties. A large number of methods have been developed for the separation of flunixin meglumine and structurally related compounds in pharmaceutical preparations, such as: thin layer chromatography, UV/VIS spectroscopy, high pressure liquid chromatography and gas chromatography. The objective of this work is to develop, optimize and validate a method for separating flunixin meglumine and structurally related substances, in solution for injection. Optimal conditions were achieved on a Agilent Zorbax Eclipse Plus C18 column (150×4.6 mm, 5 μm). The mobile phase is a mixture of 0.1% (v/v) formic acid in water and methanol in a ratio of 40:60 (v/v). The flow rate is 1.0 mL/min, the injection volume is 20 µL, the detection wavelength is 270 nm and the column temperature is 25°C. The following parameters were examined: selectivity, linearity, precision, accuracy, detection limit, quantification limit, robustness and stability of the solution. All these parameters were in line with the criteria for accepting the results. Thereafter, the method was applied to determine the content of flunixin meglumine and its impurities in the solution for injection, and the result was also in accordance with the criteria for accepting the results.